Read and gone : a haunted library mystery - Brook, Allison (Brook, Allison. Haunted library mystery ;, 2018)
"A devoted dad is as precious as diamonds, but Carrie Singleton wouldn't know since her dad Jim's been on the lam most of her life. In an unusual family reunion, she finds Jim breaking into her cottage in the middle of the night. The fun really starts when he begs her to help him recover his half of a twenty-million-dollar gem heist he pulled off with the local jeweler, Benton Parr. When she refuses, Jim takes off again. Carrie finds her father again behind bars for the recent murder of Benton Parr. Who made the connection? Unbeknownst to her, Carrie's boyfriend Dylan, an insurance investigator, has been searching for the gems. Determined to find the jewels herself, she starts examining every facet of Parr's life. She turns up a treasure trove of suspects, one of whom bashes her on the head as she's searching the victim's country cabin. Retreating to the quiet confines of the library where she works, Carrie watches as Smokey Joe, the resident cat, paws at a hole in the wall. Is he after the library's ghost Evelyn, or something shinier?" -- publisher.